The Influence of the International Economy on the Development of Democratic Values in Modern Educational Practices - Anastasiia Kostenko; Oksana Kuzmenko (Studia Warmińskie)
This article examines the urgent and crucial impact of the international economy he the development of democratic values in contemporary educational practices . The progressive development of the economy leads that changes in other spheres of society, in particular in education, where implementing democratic values becomes critical​ factor in a quality educational process. The role of value orientations and political trust in the context of the educational environment is considered, and theoretical approaches of renowned researchers such as John Dewey, Bruno Latour, Jürgen Habermas, and Anthony Giddens are analyzed. It is concluded that effective implementation of democratic values in education requires a comprehensive approach that considers the influence of the international economy, the interaction between structures and agents, and the importance of communication and network connections. Such an approach will contribute that forming a democratic, socially responsible, and economically developed society.